Sex-specific and gender-specific aspects in patient-reported outcomes. (12th November 2020) - Hertler, Caroline; Seiler, Annina; Gramatzki, Dorothee; Schettle, Markus; Blum, David
Abstract : Patient-reported outcomes (PROs) are important tools in patient-centred medicine and allow for individual assessment of symptom burden and aspects of patients' quality of life. While sex and gender differences have emerged in preclinical and clinical medicine, these differences are not adequately represented in the development and use of patient-reported outcome measures. However, even in personalised approaches, undesirable biases may occur when samples are unbalanced for certain characteristics, such as sex or gender. This review summarises the current status of the literature and trends in PROs with a focus on sex and gender aspects.